Helicobacter pylori: a long history of one clinical case - Natalya N. Dekhnich; Andrei A. Tryapyshko (LLC "MEDIAFORMAT", 2021)
The article presents a clinical case of a 44-year-old female patient F. with a diagnosis of Functional dyspepsia. Dyspepsia associated with Helicobacter pylori. Chronic gastritis associated with H. pylori. The patient has been complaining of dyspepsia, shortness of breath, vomiting for 12 years. During this time, the respiratory, cardiovascular and digestive systems were examined, but no organic pathology was revealed. Three lines of H. pylori eradication were performed. Complete clinical remission after each course of H. pylori eradication was not achieved.